Strategi Peningkatan Kesadaran Pajak Di Kalangan Generasi Muda Dalam Era Digital: Analisis Peran Teknologi Dan Pendidikan Menuju Indonesia Emas 2045 - Zega, Asokhiwa; Gea, Yosua Victorada; Zebua, Mitra Setia; Ndraha, Ayler Beniah; Ferida, Yolanda (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze tax awareness and compliance among Generation Z in Indonesia, as well as identify factors that influence their participation in supporting national tax reform. This study uses a qualitative approach to explore and deeply understand the factors that influence tax awareness among the younger generation, especially Generation Z, in the digital era. The results show that tax literacy, tax administration service quality, and access to technology-based information have a significant and positive influence on Generation Z's tax awareness and compliance. In conclusion, the implementation of technology-based tax education strategies and digital tax service innovations are necessary to support sustainable tax reform in Indonesia. The Directorate General of Taxes is expected to adopt policies that are responsive to the needs and digital characteristics of Generation Z, in order to increase their participation in the national tax system.